COVID‐digital health literacy and subjective well‐being of students in Ghana: Mediation‐moderation analyses. Issue 6 (21st November 2022) - Quansah, Frank; Ankomah, Francis; Agormedah, Edmond K.; Abieraba, Richard S. K.; Srem‐Sai, Medina; Hagan, John E.; Okan, Orkan; Dadaczynski, Kevin; Schack, Thomas
Abstract: Background: Previous research has established a strong association between COVID‐19 digital health literacy (DHL) and subjective well‐being among several populations, including students. With the growing misinformation and heightened fear of COVID‐19 among persons with an underlying medical condition, several scholars have questioned the direct relationship between DHL and well‐being. This study assessed the moderating roles of information accuracy concerns and the existence of an underlying medical condition among students. Methods: Using a cross‐sectional design, a multi‐stage sampling approach was used to select 1392 students from senior high schools in Northern Ghana who completed a questionnaire containing information on DHL, information accuracy, subjective well‐being, and underlying health condition, with reported internal consistency coefficients above 0.70. The data which was processed with SPSS version 25, was analyzed using correlation (Pearson and biserial), and Hayes' PROCESS for the moderation and mediation analyses. Results: A significant positive relationship was found between (a) DHL and subjective well‐being, (b) DHL and information accuracy concerns, and (c) information accuracy concerns and subjective well‐being. However, the prevalence of underlying health condition was negatively associated with information accuracy, DHL, and subjective well‐being. Information accuracy concerns and the existence of an underlying medical condition significantly regulated the relationship between DHL and subjective well‐being. Conclusions: Demonstrating satisfactory levels of DHL does not necessarily result in improved subjective well‐being. However, emphasis should be placed on whether individuals attach much importance to the accuracy of information retrieved as well as having or not an underlying health condition. Patient or Public Contribution: We collaborated with head teachers, teachers and students before and during the administration of the survey instrument across selected public secondary schools in the Northern and Upper Regions of Ghana.